A coupled role for CsMYB75 and CsGSTF1 in anthocyanin hyperaccumulation in purple tea. (18th December 2018) - Wei, Kang; Wang, Liyuan; Zhang, Yazhen; Ruan, Li; Li, Hailin; Wu, Liyun; Xu, Liyi; Zhang, Chengcai; Zhou, Xiaogui; Cheng, Hao; Edwards, Robert
Summary: Cultivars of purple tea ( Camellia sinensi s) that accumulate anthocyanins in place of catechins are currently attracting global interest in their use as functional health beverages. RNA‐seq of normal (LJ43) and purple Zijuan (ZJ) cultivars identified the transcription factor CsMYB75 and phi (F) class glutathione transferase CsGSTF1 as being associated with anthocyanin hyperaccumulation. Both genes mapped as a quantitative trait locus (QTL) to the purple bud leaf color (BLC) trait in F1 populations, with CsMYB75 promoting the expression of CsGSTF1 in transgenic tobacco ( Nicotiana tabacum ). Although CsMYB75 elevates the biosynthesis of both catechins and anthocyanins, only anthocyanins accumulate in purple tea, indicating selective downstream regulation. As glutathione transferases in other plants are known to act as transporters (ligandins) of flavonoids, directing them for vacuolar deposition, the role of CsGSTF1 in selective anthocyanin accumulation was investigated. In tea, anthocyanins accumulate in multiple vesicles, with the expression of CsGSTF1 correlated with BLC, but not with catechin content, in diverse germplasm. Complementation of the Arabidopsis tt19‐8 mutant, which is unable to express the orthologous ligandin AtGSTF12, restored anthocyanin accumulation, but did not rescue the transparent testa phenotype, confirming that CsGSTF1 did not function in catechin accumulation. Consistent with a ligandin function, transient expression of CsGSTF1 in Nicotiana occurred in the nucleus, cytoplasm and membrane. Furthermore, RNA‐Seq of the complemented mutants exposed to 2% sucrose as a stress treatment showed unexpected roles for anthocyanin accumulation in affecting the expression of genes involved in redox responses, phosphate homeostasis and the biogenesis of photosynthetic components, as compared with non‐complemented plants. Significance Statement: Recently developed purple tea cultivars owe their health‐promoting activities to an unusual redirection of flavonoid synthesis from catechin into anthocyanin hyperaccumulation. Using a combination of biochemistry, and molecular and classical genetics, we demonstrate that the formation of the purple pigment results from the joint expression of an MYB‐like transcription factor that enhances flux into flavonoid synthesis and a glutathione transferase (CsGSTF1) that selectively shuttles pathway intermediates from catechin into vesicular anthocyanin deposition.